2015
DOI: 10.1163/15685381-00003018
|View full text |Cite
|
Sign up to set email alerts
|

Niche segregation of sand lizard (Lacerta agilis) and green lizard (Lacerta viridis) in an urban semi-natural habitat

Abstract: Different types of semi natural habitats has important role in long-term survival and maintenance of reptile species in urban environments. Heterogeneous urban green islands can provide conditions that enable competing species to live together in relatively small areas. However, the key mechanism of coexistence could vary from types of habitats and taxa. We investigated the population structure, the fine scale habitat segregation and diel activity pattern of two lizard species (Lacerta viridis and L. agilis) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Contrary to these studies, our results show that L. viridis was more abundant in cells characterised by less tussocky vegetation and low burrow numbers. Previous works on the habitat selection of L. agilis suggested the importance of soil type and wetness (Covaciu-Marcov et al 2006), burrow availability (Török 2002), and a preference to open, bush-and treeless habitats (Nemes et al 2006;Heltai et al 2015). In our study, we found no evidence of the effect of burrow numbers on abundance on L. agilis, but we detected a preference to open and wet vegetation, characterised by high cover and vertical diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to these studies, our results show that L. viridis was more abundant in cells characterised by less tussocky vegetation and low burrow numbers. Previous works on the habitat selection of L. agilis suggested the importance of soil type and wetness (Covaciu-Marcov et al 2006), burrow availability (Török 2002), and a preference to open, bush-and treeless habitats (Nemes et al 2006;Heltai et al 2015). In our study, we found no evidence of the effect of burrow numbers on abundance on L. agilis, but we detected a preference to open and wet vegetation, characterised by high cover and vertical diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that the studied Lacerta species are present in a wide range of habitats; however, there is surprisingly limited information about the fine-scale (microhabitatlevel) requirements and preference of the studied species. The general view on the habitat of L. viridis is that it consists of grasslands interspersed with bushes, trees, particularly containing edges and ecotones between grassland and forest (Heltai et al 2015). The thermal quality of the microhabitat is also known to influence habitat selection (Korsós 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an influence of the interaction of both species on the niche of L. viridis can be expected in southern regions, where the habitat of both species overlaps (Korsós, ), due to the trend of L. viridis to inhabit more covered areas toward lower latitudinal regions. However, even in this region, analyses at a finer scale have demonstrated significant niche segregation (Babocsay, ; Heltai et al, ) that allows the coexistence of both species in the same habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, niche would still be smaller compared to the core but probably less differentiated. On the other hand, in low latitudinal regions, interactions with other lizards’ species might have a more important role in restricting the niche than it does in northern peripheries (Cahill et al, ).However, the study of the niche and microhabitat selection of several species must be carefully addressed at the proper spatial scales in order to correctly quantify possible overlaps or segregation among species (Heltai et al, ), and its effects in the intraspecific comparison of the niche of populations at peripheries with the core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation